Quanto influiscono i sistemi elettorali sulle campagne? Un'analisi comparata in nove Stati europei - Francesca Montemagno; Rossana Sampugnaro (QOE-IJES)
The demand for specific expertise to manage strategically election campaigns is growing. However, their use depends on the history of political party, on their values and on their economic resources and to the context in which the election campaign takes place. In this sphere, the electoral system produces constraints and incentives for the development of the electoral campaigns. This study aims to examine the influence of electoral system on electoral campaign style and on its management. In particular, the focus is on professionalization and personalization of electoral campaigns within a comparative approach among the European states. The data are from a comparative study on candidates (CCS). The study focuses on the candidates who participated in the most recent general elections included in the database. In particular, we selected nine countries with different electoral systems: for Candidate-based electoral system, we choice Romania, United Kingdom, Ireland and Malta; for Party-based electoral system, we examined Norway, Portugal and Italy; we also included in our analysis Hungary and Germany, which have a Mixed system with single-member constituency and closed List, which can be placed between the two previous systems. The results of the study show that the electoral systems influence the election campaigns of candidates, producing different models of mobilization.